2012
DOI: 10.3354/meps09719
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem metabolism in shallow coastal lagoons: patterns and partitioning of planktonic, benthic, and integrated community rates

Abstract: Net ecosystem metabolism (NEM) provides a quantifiable and integrative method for assessing the ecological responses of aquatic ecosystems to anthropogenic disturbance and has been shown to positively relate to nutrient enrichment in some systems. We measured NEM to determine the trophic status of 4 coastal lagoons receiving a range of nutrient loads on the Virginia/ Maryland portion of the Delmarva Peninsula, USA. From July 2007 to July 2008, we used the component technique to assess NEM by developing photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
(128 reference statements)
3
7
1
Order By: Relevance
“…1). This differs from results of previous core incubation studies in the VCR lagoons that have shown unvegetated sediments were net autotrophic during at least part of the year (McGlathery et al 2001;Tyler et al 2003;Giordano et al 2012), but agrees well with the results found by Hume et al (2011) using the eddy correlation technique (see Fig. 2).…”
Section: Discussioncontrasting
confidence: 57%
“…1). This differs from results of previous core incubation studies in the VCR lagoons that have shown unvegetated sediments were net autotrophic during at least part of the year (McGlathery et al 2001;Tyler et al 2003;Giordano et al 2012), but agrees well with the results found by Hume et al (2011) using the eddy correlation technique (see Fig. 2).…”
Section: Discussioncontrasting
confidence: 57%
“…In fact, modest net autotrophy (on a monthly basis) prevailed during the summer season at vegetated sites but not at unvegetated sites. The rates of P g and R t we estimated, which were typically between 200 and 400 mmol O 2 m −2 d −1 , are comparable to those measured in other temperate ecosystems dominated by Zostera marina (Howarth et al, 2014), and net autotrophy in these low-nutrient environments is consistent with other coastal lagoons in the region (Giordano et al, 2012;Stutes et al, 2007). While the overall metabolic balance (P g /R t ) of Chincoteague Bay is difficult to assess, given large differences in metabolic balance across a range of depths and nutrient enrichment levels, we made a simple calculation whereby the mean rates of net ecosystem metabolism at CB10 were multiplied by the area of SAV in 2015 (30 km 2 ) and rates from CB06 are multiplied by the remaining area without SAV (276 km 2 ).…”
Section: Spatiotemporal Variability In Metabolism and Relationship Wisupporting
confidence: 86%
“…This study aims to (1) examine the spatial and long‐term temporal variations of pelagic GPP, ecosystem GPP, and pelagic contribution to ecosystem production across multiple shallow‐water ecosystems in the York River, and (2) investigate the succession in ecosystem assemblages of primary producers as the response to the change of nutrient loading conceptually. The ecosystem GPP is estimated using the open water diel oxygen method (Odum ; Swaney et al ; Cole et al ; Howarth and Michaels ; Caffrey ; Staehr et al ; Giordano et al ). The open water diel oxygen method, rather than measuring ecosystem GPP directly, extrapolates the production from the in situ observed dissolved oxygen (DO) concentration data based on the mass balance of DO dynamics.…”
Section: Contribution Of Primary Producers To Either Gross or Net Primentioning
confidence: 99%